An electrochemical thermal transistor - Aditya Sood (Nature Portfolio, 2018)
Thermal transistors can enable game changing applications in energy harvesting and heat routing. Here, the authors demonstrate reversible thermal modulation of nearly 10 times by ion intercalation in MoS2 nanofilms. A new thermal microscopy technique allows operando imaging of Li ion segregation.